'Soldiers of Christ arise': Religious Nationalism in the East Midlands during World War I. (September 2014) - Bell, Stuart
<x content-type="archive" xml:space="preserve">Abstract</x> A notable feature of the war was the alacrity with which the vast majority of the population became supportive of Britain's engagement in the conflict. Most church leaders acted similarly and the Church played an important role in promoting the moral case for the declaration of war. A primary cause was the belief that Britain, whose political and ecclesiastical leaders were all children of Victorian self-confidence and optimism, had a special role in God's purposes for humanity. Once war was declared, this led to Britain being seen as the new Israel, with God indubitably on her side. Physical and spiritual war were conflated, and the singing of 'Soldiers of Christ, arise' and similar hymns reflected this. As the number of casualties grew, the identification of the conflict as a 'Holy War' was exemplified by the representation of the fallen as martyrs. The Edwardian ideals of chivalry, fair-play, justice, and sacrifice which undergirded support for the conflict all had a Christian ethical basis. Drawing largely on primary sources from the counties of Nottinghamshire and Derbyshire, it is shown that the nationalism of the First World War cannot properly be understood without taking very seriously its religious dimension.